PTH-035 EUS-guided biliary and endoluminal drainage by LAMS: initial experience from a HPB/Transplant centre. (June 2019) - Keane, Geri; Reffitt, David; Harrison, Philip; Joshi, Deepak; Devlin, John
Abstract : Introduction: Endoscopic ultrasound-guided biliary or enteral drainage is an emerging alternative to managing biliary or enteral obstruction, when endoscopic retrograde cholangiopancreatography (ERCP) or duodenal stenting fail. Recently developed electrocautery-enhanced Lumen-Apposing Metal Stents (LAMS), allow endoscopic anastomosis (Hot AXIOS™ system, Boston Scientific) to facilitate EUS guided choledochojejunostomy or gastrojejunostomy. EUS guided hepaticogastrostomy is also feasible; using a dedicated half covered biliary SEMS (Giobor® stent). The aim of this study was to assess the safety and effectiveness of these stents in gallbladder, biliary and endoluminal drainage where standard approaches have failed. Methods: Case series of EUS guided biliary or enteral drainage from a tertiary referral HPB/Liver Transplant centre between January 2017 and January 2019. Results: During the 2 year study period, 19 cases were undertaken on 14 patients; 7 Male, 7 Female. Median age 77 (range 34–91). 10 of the patients had malignant disease, 4 benign. Indications included 6 EUS guided biliary drainage with LAMS from D1, 4 EUS guided gallbladder drainage, 3 EUS wire guided rendezvous, 2 EUS guided drainage of an obstructed hepaticojejunostomy, 2 EUS guided gastrojejunostomy, 1 gastrojejunostomy stent change, 1 hepaticogastrostomy. The procedure was clinically successful in 68% (13/19) of cases. Median length of stay post procedure was 4 days (range 1–32). Adverse events occurred in 32% (6/19), 5/6 were small bile leaks, which settled clinically without need for further intervention, one case of stent displacement requiring surgical removal. Conclusion: In our experience, EUS-guided LAMS placement for novel applications, performed by experienced endosonographers was safe and feasible in selected cases of benign and malignant disease.